2022
DOI: 10.3389/fimmu.2022.1033393
|View full text |Cite
|
Sign up to set email alerts
|

High-risk genotypes for type 1 diabetes are associated with the imbalance of gut microbiome and serum metabolites

Abstract: BackgroundThe profile of gut microbiota, serum metabolites, and lipids of type 1 diabetes (T1D) patients with different human leukocyte antigen (HLA) genotypes remains unknown. We aimed to explore gut microbiota, serum metabolites, and lipids signatures in individuals with T1D typed by HLA genotypes.MethodsWe did a cross-sectional study that included 73 T1D adult patients. Patients were categorized into two groups according to the HLA haplotypes they carried: those with any two of three susceptibility haplotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
1
3
1
Order By: Relevance
“…All the authors found not significant differences in alpha diversity between T1D and healthy groups. Nevertheless, this result is not in agreement with that of other similar studies, not included in this review, in which a significantly different alpha diversity was registered, both by 16S ( 35 , 36 ) and shotgun ( 37 ) sequencing, comparing T1D and healthy subjects. In all the studies selected in this review, the beta diversity of gut microbiota was estimated.…”
Section: Discussioncontrasting
confidence: 92%
“…All the authors found not significant differences in alpha diversity between T1D and healthy groups. Nevertheless, this result is not in agreement with that of other similar studies, not included in this review, in which a significantly different alpha diversity was registered, both by 16S ( 35 , 36 ) and shotgun ( 37 ) sequencing, comparing T1D and healthy subjects. In all the studies selected in this review, the beta diversity of gut microbiota was estimated.…”
Section: Discussioncontrasting
confidence: 92%
“…In these studies some microbes are associated with higher risk of autoimmunity while others are associated with lower risk of disease (5,6). Intriguingly, Parabacteroides distasonis has, in some studies (6,53,54,71), been associated with a higher risk of developing T1D, yet was associated with protecIon in our findings. One potenIal explanaIon is that Iming of exposure to immunomodulatory microbes such as P. distasonis influences the trajectory of immune development toward tolerance or autoimmunity.…”
Section: Discussionsupporting
confidence: 51%
“…Another powerful feature of the PedsCom gnotobioIc model is the ability to determine the impact of specific microbes by reconstrucIng the community without those microbes. Since P. distasonis, AnaerosFpes sp., and C. intesFnale induced pTregs, did not induce systemic anIbodies, and are epidemiologically associated with T1D (6,(51)(52)(53)(54), we hypothesized that one or more of these three microbes is necessary for the PedsCom consorIum to protect from diabetes. To directly test this hypothesis, we generated a new six-member community, PedsCom-6, that lacks P. distasonis, AnaerosFpes sp., and C. intesFnale (Fig.…”
Section: Parabacteroides Distasonis Anaeros/pes Sp and Clostridium In...mentioning
confidence: 99%
“…These relationships are unsurprising when considering the common risk-associated HLA haplotypes by autoimmunities. For example, Prevotella copri is more abundant in RA, JIA, and T1D patients compared to controls and is also associated HLA DR3-DQ2 and DR4-DQ8 ( 98 , 99 , 120 , 131 ). This pattern makes sense when considering that HLA DR4-DQ8 is a risk-associated genotype for both RA and T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could benefit from analyzing risk haplotypes against each other to verify their similarities and differences in influence over the microbiome. Compared to low-risk or neutral haplotypes, high-risk HLA DR3-DQ2 and DR4-DQ8 are associated with higher abundance of Prevotella copri at the species level, Agathobacter, Bacteroides, Blautia, Dorea, Enterococcus, Intestinimonas, Klebsiella, Veillonella at the genus level, and Enterobacteriaceae, which includes Klebsiella, Lachnospiraceae, which includes Agathobacter, Blautia, and Dorea, and Ruminococcaceae, which includes Intestinimonas, at the family level (36,(129)(130)(131)(132). Bifidobacterium and Lactobacillus stand out as either negatively associated or in lower abundance in DR3-DQ2 and DR4-DQ8 compared to protective or neutral alleles (36,39,133,134).…”
Section: Evidence For Hlaassociated Dysbiosismentioning
confidence: 99%